SISTEM JUAL BELI RUMAH DENGAN AKAD MURABAHAH DI BTN SYARIAH DITINJAU DALAM PERSPEKTIF KEADILAN - Suprima Suprima; Heru Sugiyono; Irwan Erar Josoef; Muthia Sakti; Gladys Nun Aulia Ermansyah; Muhammad Fazli Rabbani Ramadhan (Jurnal Yuridis, 2025)
This normative legal research examines the house buying and selling system using the murabahah contract at the Bank Tabungan Negara (BTN) Syariah South Tangerang Branch Office. Using deductive methods and literature review, this study outlines seven procedural stages, from the customer's home order, through the granting of power of attorney through a wakalah contract, to the execution of the murabahah contract before a notary. The results indicate that this buying and selling practice does not fully provide fairness to customers. This unfairness is evident in the bank's dominance in unilaterally setting margins, excessively high margins compared to the cost price, and the lack of room for customer negotiation. Furthermore, there is a strict limit on repayment, which can only be made after three additional payments. This situation places customers in a weak bargaining position because they must fully comply with the bank's provisions.